Grow Smart: An Integrated Nutrition and Early Child Development Intervention Among Infants Improves Expressive Language and Reduces Anemia and Iron Deficiency in Rural India (FS08-03-19). (13th June 2019) - Hurley, Kristen; Fernandez-Rao, Sylvia; Nair, K Madhavan; Balakrishna, Nangalla; Radhakrishna, Kankipati; Ravinder, P; Tilton, Nicholas; Reinhart, Gregory; Harding, Kimberly; Black, Maureen
Abstract: Objectives: Nutritional deficiency and lack of early learning opportunities contribute to the loss of developmental potential. The objective is to evaluate the effects of an integrated nutrition and early learning intervention (ELI) on micronutrient status and the development of infants in rural India. Methods: 513 infants (6–12mo) were enrolled from 26 villages in rural India and randomized using a 2 × 2 design to receive multiple micronutrient powders (MNP containing iron, zinc, vitamins A, B2, B12, C and folic acid) vs. placebo (B2) and EL vs. control. The ELI was based on the UNICEF-developed Care for Child Development. Baseline (BL), post-intervention (6 mo) and follow-up (12 mo) evaluations included Mullens Scales of Early Learning, anthropometry, and 2 ml venous blood (BL & 12 mo). Data were analyzed using linear mixed effects regression models with random village/subject intercepts accounting for site of recruitment and repeated measures. For biomarker outcomes, main effects of MNP was assessed. P-values of <0.05 considered statistically significant. For child development outcomes, main effects of MNP and ELI were analyzed separately, and three-way interactions (MNP * ELI * midline or MNP*ELI*end line) were tested. Results: At baseline, the mean age of mothers was 22.9y (SD = 2.9) and 99.6% were married. Most mothers (84.2%) had attended some schooling. Mean infant age was 8.6 mo (SD = 2.2); 53.0% were male. Anemia prevalence was 66.4%. No significant baseline differences were found. At end line, infants in the MNP group had significantly higher hemoglobin (11 g/dl vs.10 g/dl) and ferritin (18.2ug/l vs.11.5 ug/l) values compared to infants in the placebo groups, respectively. Infants in the MNP group (mean = 39.5; SE = 0.6) versus placebo group (mean = 37.7; SE = 0.6) also scored significantly higher in expressive language and marginally higher in visual reception (mean = 42.5; SE = 0.5; P  = 0.06) and social-emotional behavior (mean = 24.1; SE = 0.2; P  = 0.052), compared to the placebo (mean = 41.1; E = 0.6, mean = 23.5; SE = 0.2, respectively). Significant interactions in visual reception and expressive language performance showed that children who received either or both interventions had better scores than children who received neither. Conclusions: Home MNP and EL interventions can improve infant MN status and development. Funding Sources: Mathile Institute for the Advancement of Human Nutrition, Nutrition International, Sackler Institute for Nutrition Science of the New York Academy of Science.